2023
DOI: 10.1097/01.ogx.0000918608.16972.a2
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Fetal Acidemia With Adverse Neonatal Outcomes at Time of Scheduled Cesarean Delivery

Abstract: Up to 30% of term labor deliveries experience fetal acidemia, a condition usually caused by hypoxia that is associated with adverse neonatal outcomes. The American College of Obstetricians and Gynecologists and American Academy of Pediatrics recommend assessing fetal umbilical artery (UA) blood gases at delivery when fetal metabolic status is in question. Although a UA pH of 7.24 to 7.28 is considered normal, the degree of acidemia associated with neonatal death is unclear. Recent data suggest that mild acidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…4 Bligard et al conducted a single-center retrospective study from 2004 to 2014 examining the association of fetal acidemia with adverse neonatal outcomes in scheduled CD, and the authors reported vasopressor use at a rate of 71.9%. 2 Rimsza et al described a higher rate of vasopressor administration in a population who underwent scheduled CD at a tertiary care center between 2014 and 2017. Notably, the authors also reported a large proportion of patients with spinal-induced hypotension—with 91.3% of individuals having a documented mean arterial pressure (MAP) > 20% below baseline despite upwards of 90% receiving vasopressors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Bligard et al conducted a single-center retrospective study from 2004 to 2014 examining the association of fetal acidemia with adverse neonatal outcomes in scheduled CD, and the authors reported vasopressor use at a rate of 71.9%. 2 Rimsza et al described a higher rate of vasopressor administration in a population who underwent scheduled CD at a tertiary care center between 2014 and 2017. Notably, the authors also reported a large proportion of patients with spinal-induced hypotension—with 91.3% of individuals having a documented mean arterial pressure (MAP) > 20% below baseline despite upwards of 90% receiving vasopressors.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was neonatal acidosis defined as an umbilical artery pH ≤ 7.1 or base excess ≤ −12 mmol, as previous studies have shown increased risk of adverse outcomes in neonates at these thresholds. 2 9 10 11 12 Secondary outcomes were composites of neonatal and maternal adverse outcomes. The composite neonatal adverse outcome (CNAO) included any of the following: neonatal death, Apgar score < 7 at 5 minutes, neonatal intensive care unit (NICU) admission > 12 hours, intubation, respiratory support > 6 hours, seizures, sepsis, HIE, or therapeutic hypothermia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations